Early experiences of accredited clinical informatics fellowships. (20th May 2016) - Longhurst, Christopher A; Pageler, Natalie M; Palma, Jonathan P; Finnell, John T; Levy, Bruce P; Yackel, Thomas R; Mohan, Vishnu; Hersh, William R
Abstract: Since the launch of the clinical informatics subspecialty for physicians in 2013, over 1100 physicians have used the practice and education pathways to become board-certified in clinical informatics. Starting in 2018, only physicians who have completed a 2-year clinical informatics fellowship program accredited by the Accreditation Council on Graduate Medical Education will be eligible to take the board exam. The purpose of this viewpoint piece is to describe the collective experience of the first four programs accredited by the Accreditation Council on Graduate Medical Education and to share lessons learned in developing new fellowship programs in this novel medical subspecialty.